Return to training and professional football competition after the sanitary alert of COVID-19 with emphasis in the analysis, management and control of training loads. Systematic review and practical proposal - Agusti, D.; Alvarez, J. (Catholic University of Valencia "San Vicente Martir", 2020)
In the year 2020, the world is facing a global emergency called COVID-19, causing sports competitions to be postponed and/or suspended, resulting in the modification of sports schedules. This has caused coachesto have to prepare individual training plans or group training at a distance in decontextualized environments and with low specificity regarding the nature of the sport. In order to analyse the main factors to be taken into account in planning the training after competition in professional footballplayers, a systematic review of scientific literature addressing the selected problem was carried out. In the first search, 155 articles were obtained, identifying a total of 37 duplicate articles, therefore, according to the established criteria, a totalof 118 articles were analysed. Of these, 30 were chosen for the investigation.As conclusions of the study, we highlight the importance of performing the correct management and distribution of training loads after training with the aim of reducing the injury rate of athletes. It would be useful to follow the different practical proposals / recommendations that we present in the research for the period after training.